Capability of Cu2ONPs/diatomite material in growth inhibition and removal of Microcystis aeruginosa in aquacultute cultivation - Dinh, Thi Nga; Dang, T. Thuy Nhung; Phan, Dinh Tuan; Pham, Thanh Luu; Tran, T. Hoang Yen; nguyen, Quoc Hien (Vietnam Journal of Science and Technology, 2021)
Cu2O nanoparticles (Cu2ONPs) with particle size of 27.4 nm deposited on diatomite (Cu2ONPs/diatomite), a new low-cost material has been used to investigate growth inhibit, and bloom preventation of cyanobacteria in eutrophic waters. Diatomite collected from natural mines was also used in the experiments. Microcystis aeruginosa strain originated from Bac Lieu shrimp pond was isolated and cultured in Z8 medium. Experiments were conducted by exposing M. aeruginosa to Cu2ONPs/diatomite and diatomite at concentrations of 0.1, 0.2, and 0.5 g/L for 72 hours and 120 hours. The results showed that the concentration of 0.5 g/L in 120 hours, Cu2ONPs/diatomite was more effective in inhibiting and removing of M. aeruginosa cells than diatomite. Therefore, Cu2ONPs/diatomite could be used as a promising material for removing cyanobacterial bloom in water for aquaculture.